(untitled) (Research, Society and Development, 2023)
Fish farming is an activity that brings many economic and social benefits to Brazil, however, it generates large volumes of waste in fish processing, and the inadequate management of these residues is a concerning environmental problem. On the other hand, these residues are an economical source of proteins and other nutrients, allowing their use in obtaining by-products, such as the preparation of flours that can be included in animal feed when processed correctly. Therefore, this study aimed to evaluate and compare the potential for flour production from tambaqui and baboon residues using two treatments: flour production with cooking (T1) and flour production without cooking (T2). The flour yields obtained from the residues of the different treatments were 13.5% and 18.0% for baboon and 12.4% and 18.0% for tambaqui (T1 and T2, respectively). The highest protein contents were observed in the flours obtained from tambaqui residues. Microbiological analyses showed the absence of Salmonella spp in the flour samples, complying with current legislation. Based on this study, it is concluded that the obtained flours meet the pre-established standards of crude protein and moisture, complying with the criteria established by RIISPOA for second-quality flours. Furthermore, these flours represent a promising alternative for the reuse of fish residues, which are often improperly discarded in the environment, causing significant negative impacts.